Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the value of [tex]\( x^3 + y^3 + 12xy \)[/tex] given that [tex]\( x + y = 4 \)[/tex], let's break it down step by step using algebraic identities.
First, recall the identity for the sum of cubes:
[tex]\[ x^3 + y^3 = (x+y)(x^2 - xy + y^2) \][/tex]
Given [tex]\( x + y = 4 \)[/tex], we can substitute:
[tex]\[ x^3 + y^3 = 4 \cdot (x^2 - xy + y^2) \][/tex]
Now, to further simplify [tex]\( x^2 - xy + y^2 \)[/tex], we use the square of the sum identity:
[tex]\[ (x + y)^2 = x^2 + 2xy + y^2 \][/tex]
Given [tex]\( x + y = 4 \)[/tex], squaring both sides gives:
[tex]\[ 16 = x^2 + 2xy + y^2 \][/tex]
We can solve for [tex]\( x^2 + y^2 \)[/tex] by rearranging the equation:
[tex]\[ x^2 + y^2 = 16 - 2xy \][/tex]
Next, we substitute [tex]\( x^2 + y^2 \)[/tex] back into our previous expression:
[tex]\[ x^3 + y^3 = 4 \cdot (x^2 - xy + y^2) = 4 \cdot [(16 - 2xy) - xy] \][/tex]
[tex]\[ x^3 + y^3 = 4 \cdot (16 - 3xy) \][/tex]
[tex]\[ x^3 + y^3 = 64 - 12xy \][/tex]
Now, to find [tex]\( x^3 + y^3 + 12xy \)[/tex]:
[tex]\[ x^3 + y^3 + 12xy = (64 - 12xy) + 12xy \][/tex]
[tex]\[ x^3 + y^3 + 12xy = 64 \][/tex]
Therefore, the value of [tex]\( x^3 + y^3 + 12xy \)[/tex] is [tex]\( \boxed{64} \)[/tex].
First, recall the identity for the sum of cubes:
[tex]\[ x^3 + y^3 = (x+y)(x^2 - xy + y^2) \][/tex]
Given [tex]\( x + y = 4 \)[/tex], we can substitute:
[tex]\[ x^3 + y^3 = 4 \cdot (x^2 - xy + y^2) \][/tex]
Now, to further simplify [tex]\( x^2 - xy + y^2 \)[/tex], we use the square of the sum identity:
[tex]\[ (x + y)^2 = x^2 + 2xy + y^2 \][/tex]
Given [tex]\( x + y = 4 \)[/tex], squaring both sides gives:
[tex]\[ 16 = x^2 + 2xy + y^2 \][/tex]
We can solve for [tex]\( x^2 + y^2 \)[/tex] by rearranging the equation:
[tex]\[ x^2 + y^2 = 16 - 2xy \][/tex]
Next, we substitute [tex]\( x^2 + y^2 \)[/tex] back into our previous expression:
[tex]\[ x^3 + y^3 = 4 \cdot (x^2 - xy + y^2) = 4 \cdot [(16 - 2xy) - xy] \][/tex]
[tex]\[ x^3 + y^3 = 4 \cdot (16 - 3xy) \][/tex]
[tex]\[ x^3 + y^3 = 64 - 12xy \][/tex]
Now, to find [tex]\( x^3 + y^3 + 12xy \)[/tex]:
[tex]\[ x^3 + y^3 + 12xy = (64 - 12xy) + 12xy \][/tex]
[tex]\[ x^3 + y^3 + 12xy = 64 \][/tex]
Therefore, the value of [tex]\( x^3 + y^3 + 12xy \)[/tex] is [tex]\( \boxed{64} \)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.